Analisis Kemampuan Berpikir Prosedural Mahasiswa Calon Guru Fisika dalam Menyusun Prosedur Percobaan Fisika - Yasiroh, Laeli; Nugroho, Sunyoto Eko; Sugianto, Sugianto (UPEJ Unnes Physics Education Journal, 2021)
This study aims to describe the procedural thinking ability of prospective teachers to develop physics experiment procedures. This research is descriptive qualitative. Samples were selected by purposive sampling techniques, namely 4th semester and 6th semester students who have attended Basic Physics 1 courses and Basic Physics Experiment 1. The subjects of this study consisted of six people, who were selected based on the ability to compose experimental procedures of physics. Researchers as the main instrument in the study are supported by the results of written tests, interview results and field notes. The results showed that procedural thinking skills in prospective teachers for type-3 (low ability group ) and type-2 (medium ability group) were able to arrange experimental procedures systematically but less detailedly, while in prospective teacher students for type-1 (high ability group) were able to arrange experimental procedures systematically, logically and in detail. The difficulties faced in arranging physics experimental procedures are lack of conceptual understanding, less experimental activities, and prospective teacher students lack of practice in designing physics experimental procedures.